Design development and research of the mobile application interface with a given set of functions - Dorogaya, A.; Tkachenko, V. (ТОВ. «Друкарня Мадрид», 2023)
The topic "Design development and research of the mobile application interface with a given set of functions" is extremely relevant nowadays.
Keywords: development; research